Implementasi Kebijakan Pariwisata Halal Di NTB (Studi Implementasi Kebijakan Peraturan Daerah Provinsi NTB No.2 Tahun 2016 Tentang Pariwisata Halal) - Rahmad Hidayat; M Awaluddin; Candra Candra (JIAP (Jurnal Ilmu Administrasi Publik), 2018)
Indonesia is indeed one of the countries that has become a tourist destination for foreign tourists. Relatively large tourist spots make Indonesia a tourist destination that is mostly hunted by foreign tourists. NTB has cultural advantages, its people are 95% Muslim, religious, a thousand mosques. This is the basic capital of NTB, optimistic that it can become a world halal tourism. Based on the results of the study, it can be concluded that: The process of implementing Halal Tourism Policy in NTB based on NTB Provincial Regulation No.2 of 2016 concerning Halal Tourism by the NTB Province Tourism Office has been going well but not yet maximally. Communication, resources, disposition and bureaucratic structure factors have been carried out to make this policy a success. While the inhibiting factors in influencing the process of implementing Halal Tourism Policy in NTB by the NTB Province Tourism Office are each lack of halal tourism objects and each lack of awareness of business people to realize the concept of halal tourism.